THE EFFECT OF COMPETENCY TO EMPLOYEE PERFORMANCE IN FISHERIES AND MARINE DEVELOPMENT OF DISTRICT PELALAWAN - Hendra, Teguh; Alfaris, Abdul Safik (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
The most important organizational resource in addition to natural resources is its human resources. In an agency or organization required a system that can support the performance of the organization. One is the ability to achieve what has been planned. One's performance is also determined by one's ability to carry out the work or tasks assigned to it. To be able to create good performance, one of the things that must be a concern is the competence that someone has in an organization. This study aims to determine the effect of competence on the performance of employees at the Department of Fisheries and Marine Pelalawan District. The number of samples in this study as many as 41 employees. The results of this study indicate that the results of the validity of the overall item statement of the variable is valid because it obtained the value rhitung> rtabel (0.308). The results of simple linear regression test obtained value Y = 12.455 + 0.635X. From result of hypothesis test on result of t test obtained tcount (5,795) bigger than ttable value (2,022) with significant level 0.000 <0.05 which means that competence have positive and significant effect to performance. And from result of test of coefficient of determination (R2) obtained value equal to 0.463 meaning contribution or contribution of influence of competence variable to performance variable equal to 0.463 or 46.3 % while the rest equal to 53.7% influenced by other variable ignored or not examined in this research